Women and Divorce in Ponorogo, East Java: Responsibility of the Husband in the Family - Muzakki, M. Harir; Rabbani Lubis, Ali Akhbar Abaib Mas; Imtinah, Anis Hidayatul (Madania: Jurnal Kajian Keislaman, 2020)
A divorce is closely related to the absence of the husband's responsibility in a family. A wife has no right to propose divorce as long as the husband, as the head of the family, can carry out his obligations materially and non-materially. This paper tries to reveal why women propose divorce and how wives view their husbands' responsibilities as the family's head. This article results from field research in the Ponorogo District and uses data derived from interviews with eight female informants who proposed a legal divorce. As the head of the family, a husband has both material and nonmaterial responsibilities to his wife. This responsibility is the husband's obligation to his wife that must be fulfilled. The husband's material obligations are to provide a living, which includes feeding, providing shelter, and clothing. Meanwhile, the nonmaterial duties are to educate, guide, protect, love, and respect. The results of this study indicate that the wives proposed for legal divorce because their husbands, as to the head of the family, do not carry out their material responsibilities; that is, they do not fulfill their obligation to provide livings for their wife. Husbands also do not meet their nonmaterial duties to their wives. Cerai gugat terkait erat dengan tidak adanya tanggung jawab suami dalam sebuah keluarga. Pada dasarnya, seorang istri tidak berhak mengajukan cerai gugat selama suami sebagai kepala keluarga dapat melaksanakan kewajibannya secara material dan non material. Artikel ini ingin mengungkap mengapa perempuan mengajukan cerai gugat dan bagaimana pandangan istri terhadap tanggung jawab suami sebagai kepala keluarga. Artikel ini merupakan hasil penelitian lapangan di Kapubaten Ponorogo dan menggunakan data yang bersumber dari hasil wawancara dengan delapan informan perempuan yang mengajukan cerai gugat. Seorang suami sebagai kepala keluarga memiliki tanggung jawab material dan non material kepada istri.  Tanggung jawab tersebut merupakan kewajiban suami terhadap istri yang harus ditunaikan. Adapun  kewajiban suami  yang bersifat material adalah memberi nafkah yang meliputi memberi makan, menyediakan tempat tinggal dan pakaian.  Sedangkan kewajiban bersifat non material adalah mendidik, membimbing, melindungi, menyayangi dan menghargai.  Hasil penelitian ini menunjukkan bahwa para istri mengajukan cerai gugat karena suami sebagai kepala keluarga tidak bertanggung jawab secara material, yakni tidak menunaikan kewajibannya memberi nafkah kepada istri.  Para suami juga tidak menjalankan kewajibannya non material kepada istrinya.